Devising a calculation method for determining the impact of design features of solar panels on performance - Hilorme, Tetiana; Nakashydze, Liliya; Tonkoshkur, Alexander; Kolbunov, Vadim; Gomilko, Igor; Mazurik, Stanislav; Ponomarov, Oleksandr (Eastern-European Journal of Enterprise Technologies, 2023)
An actual scientific and practical task related to the sustainable development of the country’s energy sector is to forecast parameters and predict the conditions of operation of solar cells and solar batteries in regular and non-regular situations. It is emphasized that this makes it possible to provide solar energy with high efficiency indicators, in particular, the indicator of profitability on invested capital in the construction of solar panels. The main specific research method is regression analysis – to build a forecast model of the total amount of generated energy of solar panels in ground installations under variable conditions of operation. An analysis of the distribution of the output data of the model by the number of solar battery modules was carried out using the example of terrestrial solar installations. To obtain empirical data, 31 objects in the Dnipropetrovsk and Zaporizhia oblasts, which have functioning solar batteries with different numbers of modules, were selected. This makes it possible to calculate the weighted average amount of generated energy during operation under variable conditions. 10 intervals of frequency values were separated with the largest range of values within the interval of 10,000–20,000 pieces of solar modules. A model of the dependence of the total amount of generated energy on the number of solar battery modules and the weighted average amount of generated energy was built based on regression analysis. It was determined that the influencing factor of the model «number of solar modules» has a positive influence on the resulting factor (productivity of solar panels), while the influencing factor «weighted average amount of generated energy» has a negative influence. However, the «number of solar modules» influence factor is more significant. The obtained results give grounds for asserting the possibility of their implementation in the energy sector